APLIKASI PELAPORAN PELAKSANAAN KEGIATAN DANA ALOKASI KHUSUS MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (Studi Kasus di Dinas PUPR Kota Payakumbuh) - Ramacos Fardela; Arif Rizki Marsa; Sri Tria Siska (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2023)
The Public Works and Spatial Planning Service or known as (PUPR of Payakumbuh is the agency in charge of public works, spatial planning, and building permits in Payakumbuh. So it is necessary to control reports on development implementation, especially in the special allocation fund (DAK) activity section, one of the activities contained in PUPR, namely managing DAK activity report data to manage financial data in the PUPR Office. At the PUPR Service, especially the subdivision of the Program, there is no application system so they still use Microsoft Office Excel, this results in errors regarding funding information in making reports due to large amounts of data and delays in preparing reports. This study aims to create a web-based DAK reporting application. The method used to build the system is Rapid Application Development (RAD), with the stages of Requirement Planning, Workshop Design and Implementation, so that system development is faster and more efficient. Application development uses PHP, in this case Laravel and MySQL. The results of the research show that the application built is easy to use, all functions are running as expected, and user needs can be met.